IMPLEMENTATION OF THE INDEPENDENT LEARNING CURRICULUM IN ELEMENTARY SCHOOL - Lubis, Syibrina Jihan; Priyadi, Maya Setia (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
This research is to obtain information about the implementation of the independent learning curriculum in elementary schools. The method used in this writing is to use a literature study by reviewing several journals that are relevant to the topics discussed qualitatively. The steps taken by the author to collect reading material in this article, are (1) collecting data relevant to the topic discussed (2) analyzing the reading material that has been obtained and concluding the main topics regarding the implementation of the merdekalearning curriculum in elementary school. The implementation of the independent learning curriculum is carried out with careful planning and is able to improve the quality of Indonesian education and can prepare graduates who excel and are able to compete globally. The key to success in implementing the merdeka learning curriculum is from school principals and teachers who must have the will to make changes. Implementation of the independent curriculum cannot be separated from the role of the school principal as a school leader who must be able to move, direct, and inspire teachers to want to change towards a better education. In addition, good cooperation is needed between teachers, school principals, agencies, parents and related parties so that the implementation of the independent curriculum in driving schools can be realized optimally.